A method for the estimation of potential evapotranspiration and/or open pan evaporation over Brazil - Reddy, S. Jeevananda; Amorim Neto, Malaquias da Silva (Pesquisa Agropecuaria Brasileira, 2014)
This paper presents a simple regression model to estimate potential evapotranspiration and/or open pan evaporation data for a wide network of stations in Brazil. The model uses the readily available data sets like geocoordinates (latitude) and precipitation as inputs. Potential evapotranspiration presents a high correlation with the precipitation during summer months and with latitude during winter months. It also shows association with longitude and elevation; the magnitude of variation appears to be very small. This model gave a R2 varying from 0.460 to 0.902 for different months. The model is also extended to weekly periods of individual years and tested with the open pan evaporation data of Bebedouro and Mandacaru. The agreement between observed and predicted values appears to be good.